Analisis Parameter Spesifik dan Nonspesifik Simplisia Daun Bawang Merah (Allium cepa L.): Analysis of Specific and Nonspecific Parameters of Shallot (Allium cepa L.) Leaves Simplicia - Neneng Dwi Yana; Burhanudin Gummay; Mauritz Pandapotan Marpaung (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2022)
Shallots are natural ingredients that are used as food enhancers for food and traditional medicines. This study aimed to analyze the specific and non-specific parameters of shallot (Allium cepa L.) Simplicia. Analysis of simplicia specific parameters in the form of material identity, organoleptic, macroscopic, and microscopic examination, levels of water-soluble extracts and ethanol soluble extracts while non-specifically in the form of a percentage of drying loss, water content, total ash, acid insoluble ash, and water-insoluble ash. The results of the research on specific parameters gave a yellowish-green simplicia color, a distinctive odor, in the form of powder, macroscopic examination of leeks elongated cylindrical, small round and hollow like a pipe, blunt leaf base, pointed leaf tip, green color, microscopic examination contained cover cells, gaps and epidermal cells, the levels for water-soluble extracts were 8.81±2.12%, the levels of ethanol-soluble compounds were 5.64±2.91%. The results of the study of non-specific parameters, the percentage of drying shrinkage was 0.89±0.57%, water content was 0.89±0.34%, total ash was 12.97±0.34%, acid-insoluble ash was 6.44±2.12%, and the water-insoluble ash content was 8.03±0.84%.